0
$\begingroup$

Prove wether or not the following series diverges or converges:

$\sum_{n=0}^\infty {(-1)^nn\over n+1}$

I am just not sure, I know if I use the absolute value test for convergence and root test it is inconclusive.

I was then thinking of using nth term test however I have the $(-1)^n$, can I just ignore that?

Any help would be greatly appreciated.

$\endgroup$
2
$\begingroup$

Hint: What can you say about $$\lim_{n\to\infty}\frac{(-1)^nn}{n+1}?$$

Look at $$\lim_{n\to\infty}\frac n{n+1}$$ first.

$\endgroup$
  • $\begingroup$ ye I know that limit goes to one meaning the sum of the absolute series diverges, however that doesnt help since that doesn't prove that the alternating series converges or diverges, right? $\endgroup$ – user2250537 Jan 23 '16 at 17:56
  • $\begingroup$ Well, since $\lim n/(n+1)=1$, $\lim (-1)^nn/(n+1)$ does not exist. $\endgroup$ – Tim Raczkowski Jan 23 '16 at 17:59
  • $\begingroup$ the limit of any alternating series does not exist right, and if it doesn't exist does that mean it 'always' diverges? $\endgroup$ – user2250537 Jan 23 '16 at 18:00
  • 1
    $\begingroup$ $\lim (-1)^n/n=0$. $\endgroup$ – Tim Raczkowski Jan 23 '16 at 18:02
  • $\begingroup$ oh ok thanks so much! $\endgroup$ – user2250537 Jan 23 '16 at 18:03
3
$\begingroup$

As ${(-1)^nn\over n+1}\not\to 0$ the series does not converge.

$\endgroup$
  • $\begingroup$ Oh so I can apply the nth term test to a series by just ignoring the $(-1)^n$ ? $\endgroup$ – user2250537 Jan 23 '16 at 17:59
  • $\begingroup$ Because if so then I understand why it diverges $\endgroup$ – user2250537 Jan 23 '16 at 17:59
  • $\begingroup$ @user2250537, the necessary condition is $\lim a_n = 0$. If this is false, maybe $\exists\lim a_n = l\ne 0$, maybe $\not\exists\lim a_n$, $\endgroup$ – Martín-Blas Pérez Pinilla Jan 23 '16 at 18:03
1
$\begingroup$

Fact. Let $\{a_n\}$ be a sequence. Then $\displaystyle\lim_{n\to\infty}a_n=0$ if and only if $\displaystyle\lim_{n\to\infty}\left\lvert a_n\right\rvert=0$

Now, we wish to investigate the convergence of $\sum a_n$ where $\displaystyle a_n=(-1)^n\frac{n}{n+1}$.

To do so, let's apply the Divergence Test.

Note that $$ \lim_{n\to\infty}\left\lvert a_n\right\rvert = \lim_{n\to\infty}\left\lvert (-1)^n\frac{n}{n+1}\right\rvert = \lim_{n\to\infty}\frac{n}{n+1} = 1 $$ It follows that $\displaystyle\lim_{n\to\infty}a_n\neq0$. Hence $\sum a_n$ diverges.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.